2001
DOI: 10.1097/00002060-200111000-00011
|View full text |Cite
|
Sign up to set email alerts
|

Return to Work for Persons with Traumatic Brain Injury

Abstract: Individuals with traumatic brain injuries experience an array of physical, cognitive, and emotional changes that often make return to preinjury employment unlikely and locating new employment difficult. The authors review the literature related to the return to work for persons with traumatic brain injuries. This includes return to work outcomes, factors influencing return to work, and vocational programs that enhance employment, including a supported employment approach. Guidelines for professionals engaged i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
66
0
3

Year Published

2003
2003
2017
2017

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 130 publications
(72 citation statements)
references
References 68 publications
2
66
0
3
Order By: Relevance
“…Matheson et al added that the demand for executive functioning on a job was positively associated with job complexity and negatively associated with job organization. Other cognitive skills (attention, memory, information processing, and verbal skills) that surfaced in this review as predictive cognitive skills were identified in the RTW literature as essential cognitive skills for effective job performance [42,54,55]. It is interesting to note that these skills were also reported to be significantly affected in patients with mild TBI [56,57].…”
Section: Discussionmentioning
confidence: 88%
“…Matheson et al added that the demand for executive functioning on a job was positively associated with job complexity and negatively associated with job organization. Other cognitive skills (attention, memory, information processing, and verbal skills) that surfaced in this review as predictive cognitive skills were identified in the RTW literature as essential cognitive skills for effective job performance [42,54,55]. It is interesting to note that these skills were also reported to be significantly affected in patients with mild TBI [56,57].…”
Section: Discussionmentioning
confidence: 88%
“…Thus, this population consists predominately of young males with a potential for employment. However, postinjury employment outcomes are disappointing [3][4][5][6]. Standardized tests of psychological distress confirm the common clinical impression that family caregivers of persons with TBI feel alienated, isolated, overwhelmed, and mentally preoccupied [6].…”
Section: Introductionmentioning
confidence: 81%
“…A brief review of return to work (RTW) literature reveals contradicting findings regarding the effect of injury severity on RTW [11][12][13]. RTW rates have been tied to injury severity [9,[13][14], although not all investigators have found a relationship between injury severity and RTW [12,[15][16].…”
Section: Introductionmentioning
confidence: 99%